SOCIO-DEMOGRAPHIC DETERMINANTS OF HUMAN DEVELOPMENT IN NIGERIA: A PANEL DATA ANALYSIS - Kuhe, David Adugh; Aniah-Betiang, Elizabeth Ishagba; Uba, Tersoo; Peter, Onuche (FUDMA Journal of Sciences, 2026)
This study examined the impact of selected socio-demographic indicators on human development in Nigeria using panel data from 1994 to 2024. The Human Development Index (HDI) was modeled as the dependent variable, while life expectancy at birth (LEB), population growth (PG), fertility rate (FR), maternal mortality rate (MMR), urbanization rate (UR), population density (PD), female labour force participation (FLP), dependency ratio (DR), and youth population (YP) served as explanatory variables. Data were sourced from credible National sources. The study employed descriptive statistics, panel unit root tests (LLC and CADF/CIPS), Johansen Fisher panel cointegration, Dynamic FMOLS, Panel Vector Error Correction Model (PVECM), and Dumitrescu-Hurlin panel causality tests. Results showed high variability and non-normality in key variables. All series were non-stationary at levels but became stationary after first differencing, confirming integration of order one, I(1). Cointegration results indicated a stable long-run relationship among HDI and the socio-demographic variables. FMOLS estimates revealed that LEB, UR, FLP, and YP positively and significantly influence HDI, whereas FR, PG, MMR, DR, and PD exert negative effects. The PVECM results indicated a strong adjustment mechanism, with approximately 78% of disequilibrium corrected annually, while short-run dynamics highlighted the importance of health, fertility, and labour factors. Causality results showed bidirectional relationships between HDI and LEB, FLP, and YP, while PG, FR, MMR, DR, and UR unidirectionally cause HDI, with no causality involving PD. The study recommends strengthening healthcare, promoting female participation, managing fertility, and investing in youth development.
Keywords: Human Development Index; Panel Cointegration; Panel Vector Error Correction Model; Panel Granger Causality; Nigeria